Radiactividad natural en la zona costera del departamento de Rocha, Uruguay - Noguera, Ana (2013)
The Uruguayan east coast shows an important heterogeneity of habitats including sand dunes, sea, underground and ground water with a wide diversity of flora and fauna . The area also has several mineral resources, which include black sand ores, with 7 million tons of heavy minerals evaluated in the Aguas Dulces-Valizas area. Black sand ores are composed by several minerals which include 0.6 % of monazite. Thus, all radionuclides belonging to the 238U and 232Th series are present. In order to evaluate the transfer of natural radioactive contamination from sand to other compartment, the gross alpha and beta activity was measured using a Analyzing miniscaler Ratemeter model PRS-5/STB-3 in sand, underground water and vegetation (Hydrocotile bonariensis Lamarck) from Valizas beach ((34º 20´ 31.42” S y 53º 47´ 19.47” O). All samples were pre-treated: the sand was dried, the water were acidified with HNO3, and cooled to 4º C for conservation and then dried, the vegetation was calcinated and the ash was measured. Standards 238U and 232Th ((IAEA RGU-1, RGTh-1) was also measured. From the specific activity and the obtained transfer coefficients, we can conclude that natural radioactive contaminants move from the sand to other compartments. The sandto- plant (H. bonariensis) transfer coefficient is the highest; but is in the range reported in the literature. Underground fresh water value is below the intervention level for drinking water (0.55Bq.l-1).